HUMAN RELATIONS AND THE USE OF NEW MEDIA TECHNOLOGY IN ORGANIZATIONAL COMMUNICATION AT PT. LANTERA SEJAHTERA INDONESIA - Barra P. Pradja; Mirza Ronda; Jamalullail (Bajang Institute, 2024)
This research was conducted to see the influence of Human Relations and the Use of New Media Technology in Organizational communication at PT. Lantera Sejahtera Indonesia. The research method used a census method with a population of 65 people. Data collection techniques using questionnaires and questionnaires consisting of 82 questions divided into 3 parts, namely human relations, the use of new media and organizational communication. Data analysis in this study used the SEM method. Hypothesis testing shows that human relations have a significant effect on organizational communication. This indicates that good human relations will contribute well to organizational communication. The use of new media in organizations has a significant effect on organizational communication. Furthermore, from the results of the hypothesis test, it can be seen that human relations and the use of new media together can affect organizational communication at PT Lantera Sejahtera Indonesia. From the results of this study, researchers provide several suggestions to improve organizational communication at PT Lantera Sejahtera Indonesia to be able to improve human relations for the better so that organizational communication becomes better. Furthermore, the use of new media can increase the effectiveness of communication built at PT. Lantera Sejahtera Indonesia